Menumbuhkembangkan UMKM di Indonesia: Analisis Faktor Pendukung Inklusi Keuangan - Ulfah, Muthia (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2024)
Financial inclusion can be an alternative to breaking the chain of poverty by supplying access to business capital financing to improve the welfare of underprivileged people who have had difficulty getting financial services from formal financial institutions. In other words, financial inclusion policies can develop new MSMEs, create job opportunities, reduce unemployment, and ultimately reduce poverty rates. Furthermore, financial inclusion can increase national income and inclusive economic growth.  The aim of this reseach is to determine the supporting factors for financial inclusion in developing MSMEs. This research is a literature review research by collecting literature from Google Scholar. The content analysis is used dor data analysis. This research found that there are 3 key factors supporting financial inclusion in developing MSMEs. These factors are financial literacy, financial technology, and empowerment. Financial literacy contributes to providing information to MSME regarding financial products as well as increasing the knowledge of MSME in financial management. Financial technology provides easy access for MSME to get the financial services. On the other hand, empowerment carried out by financial institutions that deliver microfinancing has an impact on the sustainability of MSMEs.Key Word :  Financial Inclusion, MSMEs, Financial Literacy, Financial Technology, Empowerment. Inklusi keuangan dapat menjadi alternatif dalam memutus mata rantai kemiskinan dengan menyediakan akses pembiayaan modal usaha untuk meningkatkan kesejahteraan masyarakat kurang mampu yang selama ini kesulitan mendapatkan layanan keuangan dari institusi keuangan formal. Artikel ini membahas kebijakan inklusi keuangan dapat menumbuhkembangkan UMKM baru, membuka lapangan pekerjaan, mengurangi pengangguran, dan pada akhirnya mengurangi angka kemiskinan. Lebih jauh, inklusi keuangan mampu meningkatkan pendapatan nasional dan pertumbuhan perekonomian yang inklusif.  Tujuan penelitian ini adalah untuk menggali faktor-faktor penunjang inklusi keuangan dalam menumbuhkembangkan UMKM. Penelitian ini merupakan penelitian literature review dengan mengumpulkan literatur dari google scholar. Analisis data dilakukan melalui content analysist. Penelitian ini menemukan bahwa terdapat 3 faktor kunci pendukung inklusi keuangan dalam menumbuhkembangkan UMKM. Faktor tersebut adalah literasi keuangan, teknologi keuangan, dan pemberdayaan. Literasi keuangan berkontribusi dalam memberikan informasi kepada pelaku UMKM terkait produk-produk keuangan serta meningkatkan pengetahuan pelaku UMKM dalam pengelolaan keuangan. Teknologi keuangan memberikan kemudahan akses kepada pelaku UMKM dalam mendapatkan akses layanan keuangan. Di sisi lain, pemberdayaan yang dilakukan oleh lembaga keuangan yang memberikan pembiayaan mikro berpengaruh pada keberlanjutan UMKM Kata Kunci: Inklusi Keuangan, UMKM, Literasi Keuangan, Teknologi Keuangan, Pemberdayaan.